Folkmusic and computers - Bebbington, Brian (International Library of African Music, 1968)
Nowadays one hears more and more about the use of the computer as an aid in the study of music, which is hardly surprising when one realises that all music is based on laws of logic and that computers are built to follow such laws. For example, I recently programmed an IBM 1440 computer to print a graph comparing African and European musical scales, utilising the system Dr. Tracey designed many years ago. This system is based on the fact that Africans sing notes which are not recognized in the accepted scale of twelve semitones and therefore cannot be written down accurately on conventional music paper, but can be illustrated on a graph using factors obtained from a mathematical table devised by Dr. Tracey. These factors are obtained from the table using the pitch of a note expressed in vibrations per second; this number having been established by Dr. Tracey, previously using a special set of tuning forks and more recently with the aid of a stroboscope.
Keywords: Africa; Ethnomusicology; Music; Data Processing; African Music